Some Aspects On The Biology Of Mesocyclops Asper/Conis (Copepoda, Cyclopoida) And Its Efficiency In The Control Of Vector Mosquito Larvae - Krishnan.S, Vinogiri (2007)
Mesocyclops aspericonis from the family Cyclopoida is a freshwater free-living copepod and was studied in this research. This cyclopoid is an efficient biological agent of vector mosquito larvae. The biology and its efficiency as a biological agent of mosquito larvae of this cyclopoid were examined. Through out this study, only one species was obtained, the Mesocyclops aspericonis (Daday, 1906). The behaviour and the biology of this species were observed through out the study. The production of Mesocylops aspericonis that was obtained from the sampling freshwater of paddy fields showed significant in both culture media that was prepared. When they were placed in groups of 20, 15 and 10 in each media, the freshwater media was the appropriate media in the production of the cyclopoids. Leaf foliage media was the best media in the culture when they were grouped in 5 and when only 1 gravid cyclopoid was placed. The copepods were confirmed as efficient biological agents of vector mosquitoes in this study. They were tested in both laboratory and field conditions. They were proved to be vicious predators of first and second instars of all the four vector mosquito species; Aedes aegypti, Aedes albopictus, Culex quinquefasciatus and Anopheles sp. that were tested. This tiny organism was seen maiming and eating the larvae as its food source. The Mesocyclops aspericonis suppressed the amount of third and fourth instars of the Aedes albopictus larvae in the field trial using tires as the artificial breeding containers, after a month's evaluation.